2014
DOI: 10.1039/c4nr00699b
|View full text |Cite
|
Sign up to set email alerts
|

Immune response is required for the control of in vivo translocation and chronic toxicity of graphene oxide

Abstract: Graphene oxide (GO) shows great promise as a nanomaterial for medical applications; however, the mechanism for its long-term adverse effects is still largely unclear. Here, we show that chronic GO exposure not only caused damage on the function of both primary and secondary targeted organs but also induced severe accumulation of pathogenic microbial food (OP50) in the intestine of Caenorhabditis elegans, a non-mammalian alternative toxicity assay system. GO accumulated in the intestine could be largely co-loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 65 publications
2
56
0
7
Order By: Relevance
“…Nowadays, C . elegans has been employed as a benchmark system for toxicological studies because of its high sensitivity to environmental contaminants (Leung et al ., ; Wu et al ., ). As C .…”
Section: Introductionmentioning
confidence: 97%
“…Nowadays, C . elegans has been employed as a benchmark system for toxicological studies because of its high sensitivity to environmental contaminants (Leung et al ., ; Wu et al ., ). As C .…”
Section: Introductionmentioning
confidence: 97%
“…Using C. elegans , previous studies have suggested the GO toxicity on the functions of both primary (such as intestine) and secondary (such as neuron and reproductive organs) targeted organs15161718. Regarding the cellular mechanisms of GO toxicity, the published data have suggested that GO toxicity might be consequent to the bioavailability, induction of reactive oxygen species (ROS), enhanced intestinal permeability, disrupted innate immune response, and prolonged defecation cycle length in nematodes16171920. Previous studies have also implied the crucial role of intestinal biological barrier against GO toxicity in nematodes1721.…”
mentioning
confidence: 99%
“…Regarding the cellular mechanisms of GO toxicity, the published data have suggested that GO toxicity might be consequent to the bioavailability, induction of reactive oxygen species (ROS), enhanced intestinal permeability, disrupted innate immune response, and prolonged defecation cycle length in nematodes16171920. Previous studies have also implied the crucial role of intestinal biological barrier against GO toxicity in nematodes1721. It has also been reported that the induction of oxidative stress might play a key role in the chemical mechanism for GO induced shortened longevity in exposed nematodes15.…”
mentioning
confidence: 99%
“…The classic model animal of nematode Caenorhabditis elegans is an important non-mammalian alternative for toxicological study67. Previous studies using nematodes have demonstrated that GO exposure could lead to toxic effects on the functions of both primary (such as intestine) and secondary (such as neuron and reproductive organs) targeted organs8910111213. Furthermore, the activation of oxidative stress, enhanced intestinal permeability, disrupted innate immune response, and prolonged defecation cycle length were found to contribute to the formation of GO toxicity in nematodes91011.…”
mentioning
confidence: 99%